PEMBERIAN BERBAGAI JENIS KOMPOS PADA PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L) DI KABUPATEN ENREKANG - Diana S. Susanti (AGRICOLA, 2015)
The purpose of this research is to know the influence of various types of organic matter on the growth of compost and the results of three varieties of onion plants. This study was conducted in May-July 2014 in the village of Saruran, District Anggeraja. This study used a randomized block design (RBD) factorial repeated three times. Varieties used in this research were Katumi (v1),  Batu Ijo (v2), and Maja  Cipanas (v3). First this is cow dung (O1), agricultural wates (O2), and manure + agricultural wates (O3). The result showed that combination of cow manure agricultural wastes (o3) gives the best significant effect on growth and production of onion of Batu Ijo variety. It’s effect on number of leaves, number of tubers, and fresh weight tubers.